2017
DOI: 10.1002/adhm.201700966
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Phosphate–Collagen Scaffold with Aligned Pore Channels for Enhanced Osteochondral Regeneration

Abstract: This study reports the development of a bilayered scaffold with aligned channels produced via a sequential coextrusion and unidirectional freezing process to facilitate upward bone-marrow stem-cell migration. The biomimetic scaffold with collagen and biphasic calcium phosphate (BCP) layers is successfully fabricated with matching of the cartilage and bone layers. The aligned structure results in an enhancement of the compressive strength, and the channels enable tight anchoring of the collagen layers on the BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Of note, another study by Seong et al indicated that small channels enhanced proliferation and migration in vitro and pore sizes of 270 mm were best for cell migration in vivo. 62 This could explain the lack of migration and metabolic activity differences in our scaffolds, which had average pore diameters in the range of 150-200 mm.…”
Section: Discussionmentioning
confidence: 96%
“…Of note, another study by Seong et al indicated that small channels enhanced proliferation and migration in vitro and pore sizes of 270 mm were best for cell migration in vivo. 62 This could explain the lack of migration and metabolic activity differences in our scaffolds, which had average pore diameters in the range of 150-200 mm.…”
Section: Discussionmentioning
confidence: 96%
“…This difference in results could be attributed to a difference in metabolic activity of PCL structures; however, our scaffolds had no metabolic activity differences, indicating no bias on ALP activity. Of note, another study by Seong et al indicated that small channels enhanced proliferation and migration in vitro and pore sizes of 270μm were best for cell migration in vivo 62 . This could explain the lack of migration and metabolic activity differences in our scaffolds, which had average pore diameters in the range of 150 -200 μm.…”
Section: Discussionmentioning
confidence: 99%
“…Yun-Jeong et al have shown that not only the microenvironment generated by the composition of the biomaterials impact on a better imitation of the osteochondral unit, but also the scaffolding structure has an important influence, being an aligned structure the most adequate in comparison with a randomly structured scaffold [55]. A stratified design of aligned channels in a biphasic scaffold using collagen type I and biphasic calcium phosphate (BCP) to mimic the cartilage and bone tissue, respectively, was manufactured by using an exquisite unidirectional freeze-casting process.…”
Section: Multiphasic Scaffoldingmentioning
confidence: 99%
“…Likewise, BCP provides significant osteoconductivity, bioactivity, and mechanical features [54]. However, privileging on the composition, the generation of a biphasic scaffold with a longitudinal roughness of the inner channels that serves as a guide for the correct adhesion of the cells; it results in a topography that truly emulates the osteochondral unit and shows in vivo a superior regeneration of the osteochondral tissue compared to the random structure [55].…”
Section: Multiphasic Scaffoldingmentioning
confidence: 99%